MALE SEXUAL PERFORMANCE: A EXPECTATION? - Roberto Bastos Canella, Paulo (2009)
Love is disappearing in the relationships and so, prevails the search for pleasure; so, sexual performance is always concerned. It is an almost universal desire to have a lot of satisfaction in the sexual activities. The search for pleasure in consumption civilizations turns the sexual market very profitable by offers of partners, "sexual drugs", workmanships, virtual exhibitions in ribbons, videos, DVDs or by the Web. The prices depend on the efficiency of the obtained pleasure. The pleasure collection in the obligatory relationships, inside of the family, leads to conflicts that threaten the family structure.